Formalisasi Beragama Penganut Marapu Melalui Pendidikan Formal Pada Masyarakat Kampung Tarung di Sumba Barat, NTT - Oka Wedasantara, Ida Bagus; Suarsana, I Nyoman (Humanis; Vol 23 No 2 (2019)DO - 10.24843/JH.2019.v23.i02.p12, 2019)
The classification between religion and believer by the apparatus of the Indonesia state and zendeling/missionaries creates persuasive discrimination to Marapu believer in Tarung Village. Formal education was made formalization religious instrument to Marapu believer because in the practice, students must profess which is recognized juridically by the apparatus of the Indonesian state. Formulation of the problem in this research involve (1) how the process of formalization religious to Marapu believer through formal education? and (2) how implication of formalization religious to Marapu religiousity in Tarung Village?. The formalization Marapu religious through formal education to Tarung’s people can be studied by applying the theory of  hegemony, religious conversion theory, and theological inculturation theory. While the concepts used as a reference in this research are religious formalization, Marapu, formal education, and implication. This qualitative research uses etnography research methods including the technique of collecting data through the observation, interview, literatur study and data analysis in order to process data findings.The research findings show that Marapu believer must be Christianity or Catholic in order to get formal education. Marapu as teachings without scripture, make a different interpretation in Tarung’s people, it can be an obstacle for reach of common identity. For Tarung’s people “half Marapu and half Christian/Catholic” is two principle that workable, behind the succumb strategy between Marapu leaders and Christian/Catholic leaders for the sake of certain interests. Marapu of Tarung’s people have inculturation with basic Christianity/Catholicism.